Implementation of Transformational Leadership in Improving Teacher - Desi Ratna Sari (Gestion Educativa, 2024)
Education plays an important role in nation building, through quality education the next generation can be prepared to face future challenges. Teacher performance is a key factor in realizing quality education. Teachers act as conveyors of knowledge, mentors, motivators, and role models for students. Therefore, improving teacher performance is a top priority in education management. Leadership in the school environment plays an important role in improving teacher performance, especially through transformational leadership. Transformational leadership, introduced by James MacGregor Burns and developed by Bernard M. Bass, inspires and motivates subordinates to achieve more than they thought they could. This leadership style focuses on achieving organizational goals and individual development. The implementation of transformational leadership in schools can bring significant changes in the learning and teaching environment. Transformational leaders are able to generate morale, increase commitment and foster innovation among teachers by providing a clear vision, consistent support and continuous inspiration. This research aims to explore how transformational leadership can be implemented in an educational context and its effect on improving teacher performance. Through case studies and in-depth analysis, this research provides a comprehensive understanding of the role of transformational leadership in education.